Analisis Perbandingan Metode Mean Gini dan Mean Variance dalam Pembentukan Portofolio Optimal pada Saham Perusahaan Kesehatan - Dramutia, Alfika; Rosha, Media (Journal of Mathematics UNP, 2024)
Optimal Portofolio Formation can be done using various approaches, including the Mean Gini and Mean Variance methods.The purpose of this study is to compare the performance of theMean Gini and Mean Variance methods in the formation ofoptimal portfolios. This portfolio formation uses stock data onhealth companies on the Indonesia Stock Exchange. The timeperiod used is 2021. Portfolio performance can be determinedby assessing the Sharpe Ratio. The results of the Sharpe Ratiocomparison of the Mean Gini method have superior performancebecause the value is greater, namely 0.61. while the MeanVariance Method has a smaller Sharpe Index value of-1.38.